Termination w.r.t. Q of the following Term Rewriting System could be disproven:
Q restricted rewrite system:
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
Q restricted rewrite system:
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
Using Dependency Pairs [1,15] we result in the following initial DP problem:
Q DP problem:
The TRS P consists of the following rules:
A(b(x1)) → A(c(b(x1)))
A(b(x1)) → A(a(c(b(x1))))
A(b(x1)) → C(b(x1))
B(x1) → A(x1)
A(b(x1)) → B(a(a(c(b(x1)))))
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(b(x1)) → A(c(b(x1)))
A(b(x1)) → A(a(c(b(x1))))
A(b(x1)) → C(b(x1))
B(x1) → A(x1)
A(b(x1)) → B(a(a(c(b(x1)))))
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
The approximation of the Dependency Graph [15,17,22] contains 1 SCC with 1 less node.
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ NonTerminationProof
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(b(x1)) → A(c(b(x1)))
A(b(x1)) → A(a(c(b(x1))))
B(x1) → A(x1)
A(b(x1)) → B(a(a(c(b(x1)))))
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule A(b(x1)) → A(a(c(b(x1)))) at position [0] we obtained the following new rules:
A(b(y0)) → A(c(b(y0)))
A(b(x0)) → A(a(c(a(x0))))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ NonTerminationProof
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(b(x1)) → A(c(b(x1)))
A(b(x0)) → A(a(c(a(x0))))
B(x1) → A(x1)
A(b(x1)) → B(a(a(c(b(x1)))))
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
By narrowing [15] the rule A(b(x1)) → A(c(b(x1))) at position [0] we obtained the following new rules:
A(b(x0)) → A(c(a(x0)))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ QDP
↳ Narrowing
↳ QDP
↳ Narrowing
↳ QDP
↳ NonTerminationProof
↳ QTRS Reverse
Q DP problem:
The TRS P consists of the following rules:
A(b(x0)) → A(c(a(x0)))
B(x1) → A(x1)
A(b(x0)) → A(a(c(a(x0))))
A(b(x1)) → B(a(a(c(b(x1)))))
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
Q is empty.
We have to consider all minimal (P,Q,R)-chains.
We used the non-termination processor [17] to show that the DP problem is infinite.
Found a loop by narrowing to the left:
The TRS P consists of the following rules:
A(b(x1)) → A(c(b(x1)))
A(b(x1)) → A(a(c(b(x1))))
B(x1) → A(x1)
A(b(x1)) → B(a(a(c(b(x1)))))
The TRS R consists of the following rules:
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
s = A(a(c(b(a(a(c(b(x1')))))))) evaluates to t =A(a(c(b(a(a(c(b(x1'))))))))
Thus s starts an infinite chain as s semiunifies with t with the following substitutions:
- Semiunifier: [ ]
- Matcher: [ ]
Rewriting sequence
A(a(c(b(a(a(c(b(x1')))))))) → A(a(c(b(a(c(b(x1')))))))
with rule a(x1) → x1 at position [0,0,0,0] and matcher [x1 / a(c(b(x1')))]
A(a(c(b(a(c(b(x1'))))))) → A(a(c(b(c(b(x1'))))))
with rule a(x1) → x1 at position [0,0,0,0] and matcher [x1 / c(b(x1'))]
A(a(c(b(c(b(x1')))))) → A(a(c(a(c(b(x1'))))))
with rule b(x1) → a(x1) at position [0,0,0] and matcher [x1 / c(b(x1'))]
A(a(c(a(c(b(x1')))))) → A(a(c(c(b(x1')))))
with rule a(x1) → x1 at position [0,0,0] and matcher [x1 / c(b(x1'))]
A(a(c(c(b(x1'))))) → A(a(b(x1')))
with rule c(c(x1)) → x1 at position [0,0] and matcher [x1 / b(x1')]
A(a(b(x1'))) → A(b(a(a(c(b(x1'))))))
with rule a(b(x1'')) → b(a(a(c(b(x1''))))) at position [0] and matcher [x1'' / x1']
A(b(a(a(c(b(x1')))))) → A(a(c(b(a(a(c(b(x1'))))))))
with rule A(b(x1)) → A(a(c(b(x1))))
Now applying the matcher to the start term leads to a term which is equal to the last term in the rewriting sequence
All these steps are and every following step will be a correct step w.r.t to Q.
We have reversed the following QTRS:
The set of rules R is
a(x1) → x1
a(b(x1)) → b(a(a(c(b(x1)))))
b(x1) → a(x1)
c(c(x1)) → x1
The set Q is empty.
We have obtained the following QTRS:
a(x) → x
b(a(x)) → b(c(a(a(b(x)))))
b(x) → a(x)
c(c(x)) → x
The set Q is empty.
↳ QTRS
↳ DependencyPairsProof
↳ QTRS Reverse
↳ QTRS
Q restricted rewrite system:
The TRS R consists of the following rules:
a(x) → x
b(a(x)) → b(c(a(a(b(x)))))
b(x) → a(x)
c(c(x)) → x
Q is empty.